Cryopreservation viability of methicillin-resistant Staphylococcus aureus under varying concentrations of dimethyl sulfoxide. - Gardoce, Rosthon Subron
Staphylococcus aureus is a pathogen of increasing importance due to a rise in antibiotic resistance and multidrug resistant strains of Methcillin-Resistant Staphylococcus aureus (MRSA). In a hospital, medical and agricultural setting, MRSA infestation can lead to severe problems which could even result to death. The significant impact of MRSA on public health and epidemiology suggests that a long-term preservation method is needed for extensive studies on the said species. The knowledge on the optimum cryopreservaton conditions for MRSA will be useful for long-term preservation of cell cultures for future studies. Hence, the optimum cryopreservation condition for MRSA was investigated. MRSA isolates were treated with different dimethyl sulfoxide (DMSO) concentrations ( 0 percent, 5 percent, 10 percent, 15 percent, 20 percent) at three different levels of storage temperature (4 degrees centigrade, -20 degrees centigrade, -80 degrees centigrade) for a period of 150 days. Three-Way Analysis of variance revealed that the interaction between the said factors had a significant effect on the cell viability and density of MRSA. Turkey's Test revealed that the optimum condition for cryopreservation of MRSA that maintained the highest percentage of cell viability and population is at 5 percent DMSO at -20degrees centigrade. Moreover, cryopreservation up to 30 days is the optimum condition for MRSA to be viable. Certain factors such as pH are recommended to be included in the study to further test an effective cryopreservation protocol for MRSA.